Green Initiatives and Firm Value: The Moderating Effect of Environmental Performance - Sugiyarti Fatma Laela; Nur Hendrasto; Miftakhus Surur (Jurnal Dinamika Akuntansi dan Bisnis)
This study examined the impact of green initiatives on firm value and the moderating effect of environmental performance on the relationship between the variables. The proxies of green initiatives are green innovation, eco-efficiency, green accounting, and carbon emissions disclosure, while the indicators of firm value are market capitalisation, price-to-book value, price-earnings ratio, and dividend payout ratio. Environmental performance is measured by the Environmental Performance Rating Program issued by the Indonesian Ministry of Environment and Forestry. The data were gathered from listed companies on the Jakarta Islamic Index 70 (JII-70) and the IDX-80 index over the period 2019 to 2022. The final samples consist of 66 companies (or 172 firm-year observations). Using the Partial Least Squares Structural Equation Modeling (PLS-SEM), this study found green initiatives has a positive impact on firm value when tested using the total sample as well as a separate sample of each index. However, no empirical evidence was found that environmental performance enhances the positive impact of green initiatives on firm value. The regulators should incorporate environmental performance alongside financial fundamentals into the selection process of the Jakarta Islamic index.